Early conscious prone positioning in patients with COVID-19 receiving continuous positive airway pressure: a retrospective analysis. Issue 1 (6th September 2020) - Winearls, Stuart; Swingwood, Ema L; Hardaker, Charlotte L; Smith, Amy M; Easton, Fraser M; Millington, Katherine J; Hall, Rebecca S; Smith, Ann; Curtis, Katrina J
Abstract : The global pandemic of COVID-19 has challenged the management of hypoxaemic respiratory failure and strained intensive care unit resources. While prone positioning (PP) is an established therapy in mechanically ventilated patients with acute respiratory distress syndrome (ARDS), its role in conscious patients is less well defined. We retrospectively reviewed our experience of implementing early PP in a cohort of 24 patients with acute hypoxaemic respiratory failure due to COVID-19 who required support with continuous positive airway pressure (CPAP). The use of PP alongside CPAP significantly increased both the ROX index and arterial oxygen pressure:fractional inspired oxygen (PaO2 :FiO2 ) ratio from baseline values (ROX index: 7.0±2.5 baseline vs 11.4±3.7 CPAP+PP, p<0.0001; PaO2 :FiO2 ratio: 143±73 mm Hg baseline vs 252±87 mm Hg CPAP+PP, p<0.01), and the changes to both the ROX index and PaO2 :FiO2 ratio remained significant 1 hour after cessation of proning. The mean duration of PP in the first 24 hours was 8±5 hours. Few complications were observed and PP was continued for a mean of 10±5 days. From our experience in a dedicated COVID-19 respiratory high care unit, PP alongside CPAP therapy was feasible, tolerated, safe and improved oxygenation. The use of conscious PP in ARDS warrants further investigation in randomised controlled trials.